Progression or suppression: two sides of the innate lymphoid cells in cancer - Hosseini, S. Haleh; Sharafkandi, Nadia; Seyfizadeh, Narges; Hemmatzadeh, Maryam; Marofi, Faroogh; Shomali, Navid; Karimi, Mohammad; Mohammadi, Hamed (Journal of cellular biochemistry, 2020)
Innate lymphoid cells (ILCs) as key players in innate immunity have been shown to be significantly associated with inflammation, lymphoid neogenesis, tissue remodeling, mucosal immunity and lately have been considered a remarkable nominee for either tumor-promoting or tumor-inhibiting functions. This dual role of ILCs, which is driven by intrinsic and extrinsic factors like plasticity of ILCs and the tumor microenvironment, respectively, has aroused interest in ILCs subsets in past decade. So far, numerous studies in the cancer field have revealed ILCs to be key players in the initiation, progression and inhibition of tumors, therefore providing valuable insights into therapeutic approaches to utilize the immune system against cancer. Herein, the most recent achievements regarding ILCs subsets including new classifications, their transcription factors, markers, cytokine release and mechanisms that led to either progression or inhibition of many tumors have been evaluated. Additionally, the available data regarding ILCs in most prevalent cancers and new therapeutic approaches are summarized.
03 November 2019
Gesehen am 11.05.2020